2015
DOI: 10.1002/gps.4291
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter atrophy in patients with mild cognitive impairment/Alzheimer's disease over the course of developing delusions

Abstract: Objective We conducted a neuroimaging analysis to understand the neuroanatomical correlates of gray matter loss in a group of mild cognitive impairment and early Alzheimer’s disease patients who developed delusions. Methods With data collected as part of the Alzheimer’s Disease Neuroimaging Initiative, we conducted voxel-based morphometry to determine areas of gray matter change in the same Alzheimer’s Disease Neuroimaging Initiative participants, before and after they developed delusions. Results We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Few longitudinal neuroimaging studies have investigated neural correlates of psychosis in AD. A voxel‐based morphometry (VBM) study, which investigated alterations in the grey matter volume in mild cognitive impairment (MCI) and AD patients both before and after the onset of delusions, detected significant reductions in grey matter volumes in the left posterior hemisphere (including cuneus and precuneus) and the cerebellum . Recently, Qian et al have reported a greater rate of atrophy in fronto temporal regions in AD patients with delusions .…”
Section: Introductionmentioning
confidence: 99%
“…Few longitudinal neuroimaging studies have investigated neural correlates of psychosis in AD. A voxel‐based morphometry (VBM) study, which investigated alterations in the grey matter volume in mild cognitive impairment (MCI) and AD patients both before and after the onset of delusions, detected significant reductions in grey matter volumes in the left posterior hemisphere (including cuneus and precuneus) and the cerebellum . Recently, Qian et al have reported a greater rate of atrophy in fronto temporal regions in AD patients with delusions .…”
Section: Introductionmentioning
confidence: 99%
“…Our group also looked at this question with respect to delusions and found cross-sectionally grey matter volume loss increased in the right-frontal-temporal region [22]. We also examined patients longitudinally and found atrophy more pronounced in regions corresponding to the default mode network and cerebellum [23]. As none of the regions identified to date correspond to areas of atrophy in AD, combined they suggest a different mechanism may underlie the development of delusions in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Analysing patients more than one year (and up to three years) before conversion, 2 VBM studies found no changes in the frontal lobe. 43 , 46 The findings for GM loss in MCI and AD patients are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%